Standing in the Shadows of Obesity: The Local Food Environment and Obesity in Detroit. (28th November 2016) - Ledoux, Timothy F.; Vojnovic, Igor; Manning Thomas, June; Pothukuchi, Kameshwari
Abstract: Much of the literature examining associations between local food environments and obesity fail to consider whether or not respondents actually utilise the food stores around them. Drawing on survey data, this study examines the relationships between the neighbourhood food environment, mobility and obesity among residents from the lower eastside neighbourhoods of Detroit, Michigan. Certain dimensions of the local food environment are found to contribute to obesity, but these dimensions occur at different scales. Residents who rely on their immediate neighbourhood food environment have a higher likelihood of being obese than residents who do not utilise the stores around them. At a broader level, lower eastside Detroit residents with a greater concentration of fast food establishments around them have a higher possibility of being obese than residents with fewer fast food restaurants around them. The salience of the fast food environment warrants additional attention in terms of public health interventions.